Cardiac Involvement in Classical Organic Acidurias: Clinical Profile and Outcome in a Pediatric Cohort - Silvia Passantino; Serena Chiellino; Francesca Girolami; Mattia Zampieri; Giovanni Battista Calabri; Gaia Spaziani; Elena Bennati; Giulio Porcedda; Elena Procopio; Iacopo Olivotto; Silvia Favilli (Diagnostics, 2023)
Background: Cardiac involvement is reported in a significant proportion of patients with classical organic acidurias (OAs), contributing to disability and premature death. Different cardiac phenotypes have been described, among which dilated cardiomyopathy (DCM) is predominant. Despite recent progress in diagnosis and treatment, the natural history of patients with OAs remains unresolved, specifically with regard to the impact of cardiac complications. We therefore performed a retrospective study to address this issue at our Referral Center for Pediatric Inherited Errors of Metabolism. Methods: Sixty patients with OAs (propionic (PA), methylmalonic (MMA) and isovaleric acidemias and maple syrup urine disease) diagnosed from 2000 to 2022 were systematically assessed at baseline and at follow-up. Results: Cardiac anomalies were found in 23/60 OA patients, all with PA or MMA, represented by DCM (17/23 patients) and/or acquired long QT syndrome (3/23 patients). The presence of DCM was associated with the worst prognosis. The rate of occurrence of major adverse cardiac events (MACEs) at 5 years was 55% in PA with cardiomyopathy; 35% in MMA with cardiomyopathy; and 23% in MMA without cardiomyopathy. Liver transplantation was performed in seven patients (12%), all with PA or MMA, due to worsening cardiac impairment, and led to the stabilization of metabolic status and cardiac function. Conclusions: Cardiac involvement was documented in about one third of children diagnosed with classical OAs, confined to PA and MMA, and was often associated with poor outcome in over 50%. Etiological diagnosis of OAs is essential in guiding management and risk stratification.